An aerosol type ultrasonic coupling agent and a preparation method thereof
Patent Information
- Application Number
- CN202611100166.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-30
AI Technical Summary
[0011]本申请针对现有气雾型超声耦合剂存在的喷出性能与驻留性能难以兼顾、喷后易流挂、膜层连续性不足以及长期扫描过程中易失水的问题,并区别于传统单一增稠体系,本申请采用通过一种气雾型超声耦合剂及其制备方法,利用剪切变稀多糖、纤维素衍生物、保水聚合物以及层状硅酸盐纳米片组成的复合功能网络
1、本发明的气雾型超声耦合剂通过剪切变稀多糖、纤维素衍生物、保水聚合物与层状硅酸盐纳米片的协同配合,构建了可逆触变网络。该网络在气雾喷出的高剪切条件下黏度大幅下降,保证顺畅喷射;喷出后层状硅酸盐纳米片网络迅速重建以提供初始屈服应力,有效抑制流挂,同时多糖网络逐步恢复缠结,将离散液滴融合为均匀、连续的耦合膜,从而能够兼顾了良好的雾化喷射性和优异的驻留定型能力。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of ultrasonic coupling agent technology, and more specifically to an aerosol-type ultrasonic coupling agent and its preparation method. Background Technology
[0002] Ultrasound coupling agents are indispensable auxiliary materials in ultrasound diagnosis and ultrasound therapy. However, traditional gel-type ultrasound coupling agents are usually applied via bottle compression. In actual clinical applications, medical staff need to manually squeeze and apply them to the examination site, which is not only inconvenient but also prone to problems such as bottle contamination, cross-contamination, and material waste during continuous examinations for multiple patients. Therefore, developing novel ultrasound coupling agents that are easy to release quickly and apply precisely has become an important direction for development in this field.
[0003] To address the aforementioned issues, existing technologies have proposed aerosol-type ultrasound coupling agents. For example, existing technical document CN106039329A discloses an aerosol-type medical ultrasound coupling agent, which employs a pouch-type aerosol packaging structure to store the coupling agent within an aerosol can. It is ejected via propellant pressure and utilizes traditional gel components such as carbomer, glycerin, and triethanolamine to form a sprayable coupling agent system. This technical solution solves the problem of inconvenience in using traditional squeeze-type coupling agents, achieving rapid ejection and convenient application of the coupling agent.
[0004] The aforementioned aerosol-type ultrasonic coupling agents still primarily rely on traditional single-polymer thickening systems to increase viscosity, while the aerosol spraying process requires the composition to have low flow resistance. Increasing the polymer concentration to enhance post-spraying retention performance leads to increased system viscosity, increased spraying resistance, and even nozzle clogging; conversely, reducing viscosity to improve spraying performance easily results in problems such as post-spraying liquid film flow, sagging, and inability to maintain a continuous coupling layer. Therefore, existing aerosol-type coupling agents struggle to simultaneously meet the requirements of both spraying performance and stable post-spraying retention.
[0005] Furthermore, existing technologies have also conducted further research on spray-type ultrasonic coupling agents. For example, US11311635B2 discloses an ultrasonic coupling spray composition that uses a starch-based thickener to increase the system viscosity and reduces the tendency to form aerosols by controlling the size of the spray droplets. This technology points out that the spray system needs to strike a balance between thickening properties and sprayability, while also addressing the potential precipitation problem caused by starch systems.
[0006] However, the aforementioned technologies still have certain shortcomings. First, starch-based thickening systems mainly rely on a single polymer chain structure to provide viscosity regulation, which limits their ability to handle rapid viscosity changes during jet shearing and their ability to recover structure after jetting. Second, to improve system stability, auxiliary components such as oils, emulsifiers, or starch-degrading enzymes need to be added, leading to increased formulation complexity. Furthermore, simply increasing the thickener content to control droplet size can easily reduce the system's flow properties, making it difficult to simultaneously achieve continuous film formation and acoustic coupling stability.
[0007] Furthermore, existing technologies have proposed improving the post-use cleaning of coupling agents through film formation. For example, CN107854696B discloses a conjunctival type medical ultrasound coupling agent that uses a polymer system to form a peelable film after use, thereby reducing the inconvenience of wiping and cleaning traditional coupling agents. This technology can improve the post-use cleaning problem, but its focus is on forming a peelable film, and it does not optimize for the shear response performance required during aerosol spraying and the rapid recovery performance after spraying.
[0008] Furthermore, existing technologies utilize alginate systems in conjunction with astringents to achieve rapid gelation. For example, CN102451475B discloses an ultrasonic coupling agent and its matching astringent system, which achieves rapid curing through the interaction of sodium alginate with divalent metal ions, thus facilitating removal. However, this technology requires additional spraying of the astringent, representing an externally triggered curing method, and cannot achieve dynamic viscosity adjustment of the coupling agent system itself during the spraying process.
[0009] In summary, existing ultrasonic coupling agent formulations typically optimize a single aspect such as spraying convenience, antibacterial properties, film-forming properties, or moisturizing properties. There is a lack of systematic synergistic design among the functional components, and a composite functional formulation system that can simultaneously meet the requirements of shear thinning, rapid structural recovery, low-bubble continuous film formation, and stable acoustic coupling performance has not yet been formed.
[0010] Therefore, there is an urgent need to develop a new aerosol-type ultrasonic coupling agent. Summary of the Invention
[0011] This application addresses the problems of existing aerosol-type ultrasonic coupling agents, such as difficulty in simultaneously achieving good ejection and retention performance, easy sagging after spraying, insufficient film continuity, and easy water loss during long-term scanning. Unlike traditional single thickening systems, this application employs an aerosol-type ultrasonic coupling agent and its preparation method, utilizing a composite functional network composed of shear-thinning polysaccharides, cellulose derivatives, water-retaining polymers, and layered silicate nanosheets. Specifically, the shear-thinning polysaccharides provide a flexible chain entanglement structure, enabling low-viscosity ejection under high shear conditions; the layered silicate nanosheets provide a reversible physical cross-linking structure, enabling rapid structural recovery after spraying; the cellulose derivatives regulate the organic-inorganic interface, improving film continuity; and the water-retaining polymer maintains the coupling film in a long-term moist state. These components are not simply superimposed, but rather work synergistically in terms of structural recovery speed, film formation process, and moisture retention, giving the resulting aerosol-type ultrasonic coupling agent easy ejection, rapid shaping, continuous film formation, and stable acoustic coupling performance. The following technical solution is provided: An aerosol-type ultrasonic coupling agent, comprising a base component and a functional component, wherein the functional component comprises shear-thinning polysaccharide, cellulose derivative, water-retaining polymer, and layered silicate nanosheets, and the base component comprises water and an acoustic modifier; wherein the acoustic modifier is selected from one or more of glycerol, propylene glycol, 1,3-propanediol, and polyethylene glycol.
[0012] Furthermore, the shear-thinning polysaccharide is selected from one or more of xanthan gum, gellan gum, konjac glucomannan, guar gum, modified guar gum, alginate, and carrageenan; The cellulose derivative is selected from one or more of hydroxyethyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose, methyl cellulose, and hydroxypropyl cellulose; The water-retaining polymer is selected from one or more of sodium hyaluronate, potassium hyaluronate, carboxymethyl chitosan, polyglutamate, trehalose polymer, and polyethylene glycol derivatives; The layered silicate nanosheets are selected from one or more of synthetic layered lithium magnesium silicate and layered aluminum magnesium silicate.
[0013] Furthermore, the shear-thinning polysaccharide is xanthan gum; the cellulose derivative includes hydroxyethyl cellulose and / or hydroxypropyl methyl cellulose; the water-retaining polymer is sodium hyaluronate; and the layered silicate nanosheets are layered lithium magnesium silicate.
[0014] Further, by weight, it includes 0.05-0.40 parts of shear-thinning polysaccharide, 0.05-0.80 parts of cellulose derivative, 0.005-0.20 parts of water-retaining polymer, 0.01-0.30 parts of layered silicate nanosheets, 12-30 parts of moisturizing acoustic modulator, and 100 parts of water.
[0015] Furthermore, the functional components also include a wetting agent and a defoamer. The wetting agent is selected from one or more of poloxamer 188, poloxamer 407, polysorbate, alkyl glycoside, and polyoxyethylene hydrogenated castor oil. The defoamer is selected from one or more of simethicone, polydimethylsiloxane emulsion, dimethicone, and siloxane polyether copolymer. By weight, the wetting agent is 0.01-0.3 parts and the defoamer is 0.005-0.15 parts.
[0016] Furthermore, the basic components also include one or more of a pH adjuster, a buffer, a chelating agent, or a preservative; wherein the pH adjuster is triethanolamine; the buffer is selected from one or more of a citrate buffer, a phosphate buffer, and a borate buffer; the chelating agent includes disodium edetate; the preservative is one or more of phenoxyethanol, ethylhexylglycerin, or potassium sorbate; and the pH of the aerosol-type ultrasonic coupling agent composition is 6.0-7.2.
[0017] A method for preparing an aerosol-type ultrasonic coupling agent includes the following steps: S1, Disperse layered silicate nanosheets in a portion of water to obtain a dispersion; S2, mix the shear-thinning polysaccharide, cellulose derivative and water-retaining polymer, and then mix with the acoustic modulator to obtain a polymer wet material; S3, after mixing the wet polymer material with the dispersion, it is then mixed with the remaining water to obtain an aerosol-type ultrasonic coupling agent; S4, the aerosol ultrasonic coupling agent is stored in the aerosol can through the bag in an isolated manner, and the propellant is filled between the aerosol can and the bag.
[0018] Furthermore, in S3, the polymer wet material is mixed with the dispersion and then matured at a temperature of 20℃-45℃ for 1-24 hours.
[0019] Furthermore, after aging, wetting agents, defoamers, pH adjusters, buffers, chelating agents, and preservatives are added when mixing with the remaining water.
[0020] Further, the aerosol-type ultrasonic coupling agent is degassed and homogenized.
[0021] Due to the adoption of the above technical solutions, the beneficial technical effects of the present invention are as follows: 1. The aerosol-type ultrasonic coupling agent of the present invention constructs a reversible thixotropic network through the synergistic cooperation of shear-thinning polysaccharides, cellulose derivatives, water-retaining polymers, and layered silicate nanosheets. This network exhibits a significant viscosity reduction under the high shear conditions of aerosol ejection, ensuring smooth spraying. After ejection, the layered silicate nanosheet network rapidly reconstructs to provide initial yield stress, effectively suppressing sagging. Simultaneously, the polysaccharide network gradually recovers its entanglement, fusing discrete droplets into a uniform and continuous coupling film, thus achieving both excellent atomization and spraying properties and superior retention and shaping capabilities.
[0022] 2. Cellulose derivatives act as a bridge and backbone reinforcement between organic polysaccharide chains and inorganic nanosheets, significantly improving the uniformity of the network and the continuity of the membrane. The water-retaining polymer efficiently converts free water in the system into bound water, greatly enhancing the water retention capacity of the coupling membrane. This allows the membrane to remain moist, soft, and continuous during long-term ultrasonic scanning, effectively avoiding the introduction of dry cracks and air gaps, ensuring stable and low-attenuation acoustic transmission performance, significantly reducing ultrasonic artifacts, and improving imaging quality.
[0023] 3. The preparation method provided by this invention first pre-disperses layered silicate nanosheets to form a uniform sheet dispersion, then pre-wets the shear-thinning polysaccharide, cellulose derivative, and water-retaining polymer with an acoustic modulator, and then combines the two and ripens them under specific conditions. This stepwise construction process ensures uniform dispersion of each component and full formation of the interpenetrating network. The method conditions are controllable, the steps are simple, the resulting product has excellent batch stability, and it is easy to realize industrial production. Detailed Implementation
[0024] To enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Based on the embodiments in this application, other similar embodiments obtained by those skilled in the art without creative effort should all fall within the scope of protection of this application.
[0025] Unless otherwise specified in the examples, standard conditions or conditions recommended by the manufacturer should be followed. Reagents or instruments whose manufacturers are not specified are all commercially available products. Unless otherwise specified, all reagents used in the examples are commercially available.
[0026] An aerosol-type ultrasonic coupling agent, comprising a base component and a functional component, wherein the functional component comprises shear-thinning polysaccharide, cellulose derivative, water-retaining polymer, and layered silicate nanosheets; and the base component comprises water and an acoustic modifier; wherein the acoustic modifier is selected from one or more of glycerol, propylene glycol, 1,3-propanediol, and polyethylene glycol. The shear-thinning polysaccharide, cellulose derivative, water-retaining polymer, and layered silicate nanosheets form a reversible thixotropic network in the basic components, causing the aerosol-type ultrasonic coupling agent to shear-thinnify during aerosol spraying and restore viscosity after spraying to form a continuous film phase.
[0027] The core innovation of the aerosol-type ultrasonic coupling agent of this invention lies in the reversible thixotropic network formed by the shear-thinning polysaccharide, cellulose derivative, and layered silicate nanosheets. The water-retaining polymer is embedded within this thixotropic network to regulate its water content and interfacial lubrication properties. This network is not a simple superposition of the functions of each component, but rather a complex system with complementary structures and synergistic functions formed through the physical interactions between the components. This simultaneously satisfies the comprehensive requirements of the aerosol-type ultrasonic coupling agent for atomization, retention and anti-sagging properties, film continuity, and acoustic transmission performance. The functions of each component in the synergistic network and the reasons why each is indispensable are described below.
[0028] (1) Interpenetration of a double network between shear-thinned polysaccharides and layered silicate nanosheets Shear-diluted polysaccharides (represented by xanthan gum) form flexible three-dimensional physical networks in solution through intermolecular hydrogen bonds and chain entanglement. Under high-speed shearing, the viscosity of this network decreases significantly due to the orientation of molecular chains along the flow field and the dissociation of entanglement points. After shearing is removed, the chain segments return to disordered entanglement, and the viscosity gradually recovers. Layered silicate nanosheets (represented by synthetic layered lithium magnesium silicate) form two-dimensional nanosheets with permanent surface charges after being exfoliated in water. When at rest, they form a card-house-like inorganic network with moderate yield stress and structural recovery ability through edge-face electrostatic attraction. During shearing, this structure rapidly disintegrates and the viscosity drops sharply. After shearing stops, the structure is rapidly reconstructed by electrostatic drive.
[0029] When shear-thinning polysaccharides are used alone, the viscosity recovery after shearing is slow and the network yield stress after recovery is low, making it difficult to prevent the sprayed droplets from sagging on the skin. When nanosheets are used alone, although the network can rebuild quickly and provide high yield stress, the resulting film is too rigid and lacks flexibility, making it prone to cracking due to drying shrinkage, resulting in poor film continuity. This invention combines the two to construct a hybrid structure in which a flexible organic network and a rigid inorganic network interpenetrate. In this interpenetrating network, the nanosheet network recovers and rebuilds its structure within a short timescale after spraying, giving the deposited droplets a high initial yield stress and effectively suppressing sagging. The xanthan gum network then gradually completes the re-entanglement of molecular chains, pulling and fusing the discrete droplets anchored by the nanosheets into a continuous and uniform coupled film. The recovery dynamics of the two complement each other on a timescale, achieving rapid shaping and ordered thixotropic behavior for subsequent film formation.
[0030] (2) Introduction of cellulose derivatives While the interpenetrating network of xanthan gum and nanosheets possesses thixotropic properties, a certain interfacial difference exists between the organic and inorganic phases at the microscale, and high dosages are often required to achieve the desired thixotropic performance. Cellulose derivatives (represented by hydroxyethyl cellulose and / or hydroxypropyl methyl cellulose) possess both hydrophilic hydroxyl groups and hydrophobic substituents on their molecular chains, enabling them to bridge the shear-thinning polysaccharide chains and nanosheet surfaces through hydrogen bonding and hydrophobic interactions, acting as compatibilizers and framework reinforcing agents. Their beneficial effects are twofold: firstly, the bridging effect of cellulose derivatives improves the structural contribution efficiency of network components per unit mass, allowing for the attainment of equivalent thixotropic and yield properties while reducing the dosage of shear-thinning polysaccharides and nanosheets, thus helping to reduce formulation costs and minimize acoustic attenuation that may be caused by high concentrations of inorganic nanosheets; secondly, as highly efficient film-forming agents, cellulose derivatives fill the microscopic gaps in the dual network, making the density and acoustic impedance of the entire system more spatially uniform, reducing the risk of phase separation between organic and inorganic components, and making the coupled membrane structure more continuous and stable.
[0031] (3) Introduction of water-retaining polymers The thixotropic network composed of shear-thinning polysaccharides and nanosheets contains numerous micron- to nanometer-sized pores. Free water within these pores easily evaporates and is lost during ultrasound examinations (especially under conditions of probe movement and surface heating), leading to shrinkage and cracking of the coupling membrane, resulting in loss of coupling continuity and the introduction of air gaps. Simply increasing the system's water content cannot fundamentally solve this problem, as excessive free water dilutes the network, reduces yield stress, and compromises anti-sagging properties. Water-retaining polymers (represented by sodium hyaluronate) possess extremely high water-binding capacity. The carboxyl and hydroxyl groups on the sodium hyaluronate molecular chain can bind water molecules through hydrogen bonding, enhancing the system's water retention capacity. In the synergistic network, sodium hyaluronate molecules fill the pores of the interpenetrating network, converting easily lost free water into bound and confined water, allowing the coupling membrane to remain moist, flexible, and continuous even under prolonged probe scanning. More importantly, the water-rich viscoelastic interface layer formed by sodium hyaluronate can adapt to the micro-texture of the skin and the nanoscale undulations of the probe's acoustic lens surface, reducing the micro-air gap between the probe and the skin interface, thereby achieving a near-ideal acoustic coupling interface and minimizing acoustic reflection and artifacts.
[0032] In summary, all four functional components described in this invention are indispensable, and their synergistic mechanism can be summarized as follows: This invention constructs a reversible thixotropic network through shear-depleting polysaccharides, cellulose derivatives, and layered silicate nanosheets. The shear-depleting polysaccharides provide a flexible chain entanglement structure, reducing the viscosity of the composition during high-shear spraying. The layered silicate nanosheets provide structural recovery capabilities through reversible physical interactions between the layers, enabling the sprayed composition to quickly recover its anti-sagging properties. The cellulose derivatives further enhance the interfacial stability between the organic components and the inorganic layers, improving film continuity. The water-retaining polymer improves water retention and interfacial lubrication properties, keeping the formed coupling film in a long-term moist state. Therefore, this composite system can simultaneously meet the requirements of aerosol sprayability, post-spray shaping, continuous film formation, and ultrasonic coupling stability. Furthermore, the shear-thinning polysaccharide is selected from one or more of xanthan gum, gellan gum, konjac glucomannan, guar gum, modified guar gum, alginate, and carrageenan; The cellulose derivative is selected from one or more of hydroxyethyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose, methyl cellulose, and hydroxypropyl cellulose; The water-retaining polymer is selected from one or more of sodium hyaluronate, potassium hyaluronate, carboxymethyl chitosan, polyglutamate, trehalose polymer, and polyethylene glycol derivatives; The layered silicate nanosheets are selected from one or more of synthetic layered lithium magnesium silicate and layered aluminum magnesium silicate.
[0033] This further defines the specific types of each functional component. Although the above substances belong to their respective functional categories, they differ in molecular structure, charge density, chain rigidity, hydrophilicity / hydrophobicity, and interaction modes with other components. Therefore, the thixotropic recovery rate, film-forming mechanical properties, and acoustic matching of the system can be flexibly adjusted according to different ultrasound examination conditions (such as probe frequency, scan duration, skin condition, etc.).
[0034] Xanthan gum has a rigid double helix conformation, which can form a through network at extremely low concentrations. It exhibits significant shear thinning behavior and yield stress, and the network recovers rapidly after shearing. It also has excellent tolerance to salt and pH changes, making it the preferred framework for constructing this system with rapid shaping and high anti-sagging properties, suitable for general testing applications.
[0035] Gellan gel can form gels with different textures depending on the degree of deacylation: low-acyl forms form rigid and brittle gels, while high-acyl forms form soft and elastic weak gels. Using gellan gel can make the continuous film formed after spraying closer to the gel state, with a firm structure, which is especially suitable for ultrasound examinations that require long-term residence without displacement.
[0036] Konjac glucomannan and xanthan gum have a strong synergistic thickening effect. A small amount of its introduction can significantly improve the final strength and cohesion of the interpenetrating network, which helps to form a more resilient continuous film and effectively prevents the coupling film from being easily squeezed apart when the probe moves, thus ensuring the continuity of coupling under dynamic scanning.
[0037] Guar gum and modified guar gum have high thickening efficiency, but natural guar gum has drawbacks such as slow hydration rate and a tendency to form insoluble flocculation. Using hydroxypropyl modified guar gum can significantly improve its solubility and transparency, providing an economical and fast-dissolving thixotropic thickening option for formulations, which helps to reduce overall costs.
[0038] Alginate can instantly form an ionic cross-linked gel upon contact with divalent metal cations. This property can be used to introduce a post-triggered reinforcement mechanism into the system: even without the addition of calcium ions, the surface strength of the coupling membrane will further increase after contact with sweat or a slightly alkaline environment on the skin surface, enhancing the retention and locking effect.
[0039] Carrageenan can form gels ranging from hard and brittle to soft and viscoelastic depending on its type (κ-, ι-, λ-). The high density of sulfate groups on its molecules gives the network a stronger charge density, which is beneficial for enhancing electrostatic interactions with positively charged components.
[0040] Hydroxyethyl cellulose and hydroxypropyl methyl cellulose are both nonionic cellulose ethers, exhibiting excellent compatibility with the charged nanosheets and xanthan gum in the system. They are not prone to microscopic phase separation due to electrostatic association, ensuring the optical and acoustic uniformity of the network. Hydroxypropyl methyl cellulose also possesses thermogelation properties, which can moderately enhance the network structure at body surface temperatures, making it the optimal combination for ensuring the uniformity and stability of this system.
[0041] Sodium carboxymethyl cellulose is an anionic cellulose derivative. Its carboxyl groups can undergo moderate electrostatic cross-linking with the positive charge on the edge of layered silicate nanosheets, thereby further enhancing the overall strength of the network. However, because it is sensitive to ionic strength and pH, it is more suitable for formulations where the electrolyte content is strictly controlled.
[0042] Methylcellulose and hydroxypropylcellulose have relatively stronger hydrophobicity. Introducing them into the system can regulate the hydrophilic-hydrophobic balance of the coupling membrane, giving the membrane a certain degree of hydrophobic barrier properties, slowing down the rate of water evaporation, and making it easier to peel off and remove as a whole after inspection.
[0043] Sodium and potassium hyaluronate can form a viscoelastic hydrated layer with both high water retention and good tactile feel in the network gaps. Their molecular chains are highly extended under spray shear, which helps to reduce atomization viscosity. In addition to its excellent water retention capacity, carboxymethyl chitosan's molecular chains carry a positive charge under weakly acidic to neutral conditions, which can form a tighter electrostatic coating layer with negatively charged nanosheets, further enhancing the bonding force of the organic-inorganic interface and improving the overall mechanical strength of the coupling film.
[0044] Polyglutamate has an extremely high water absorption rate and excellent film-forming properties, and can provide a polyamino acid-based moisturizing framework. When used in combination with sodium hyaluronate, it is expected to produce a synergistic water-locking effect, further improving the moisturizing durability of the coupling membrane under long-term scanning.
[0045] While providing water retention, trehalose polymers also act as biological structural protectants, stabilizing the natural conformation of biomacromolecules and network structures. This helps prevent structural instability and performance degradation of the components of the coupling agent during long-term storage or use under conditions of large temperature variations.
[0046] Through functional design of molecular weight and end groups, polyethylene glycol derivatives can serve as auxiliary acoustic modulators or surfactants while achieving water retention, which helps reduce the number of independent additives in the formulation and reduce the complexity of the formulation.
[0047] Synthetic layered lithium magnesium silicate has a nanoscale sheet structure that can be completely peeled off in water to form a highly transparent dispersion. Its network structure can be disintegrated and reconstructed extremely quickly, and its thixotropic properties are the most prominent. It is an ideal inorganic functional filler for the rapid shaping of this invention.
[0048] Synthetic layered magnesium aluminum silicate monolayers have relatively large particle sizes and may have slightly lower transparency than the former, but they have a significant cost advantage and also possess excellent thixotropic suspension and network reconstruction capabilities. They are suitable for high-volume consumable coupling agent applications where transparency requirements are not stringent and cost-effectiveness is the primary concern.
[0049] Furthermore, the shear-thinning polysaccharide is xanthan gum; the cellulose derivative includes hydroxyethyl cellulose and / or hydroxypropyl methyl cellulose; the water-retaining polymer is sodium hyaluronate; and the layered silicate nanosheets are layered lithium magnesium silicate.
[0050] Through extensive experimental screening, this invention has discovered that when the shear-thinning polysaccharide is xanthan gum, the cellulose derivative includes hydroxyethyl cellulose and / or hydroxypropyl methyl cellulose, the water-retaining polymer is sodium hyaluronate, and the layered silicate nanosheets are layered lithium magnesium silicate, the reversible thixotropic network formed by these four components achieves optimal overall performance, constituting the most preferred embodiment of this invention. The underlying mechanism lies in the fact that this combination achieves a high degree of matching among the four components in four dimensions: charge characteristics, hydrophilicity / hydrophobicity, recovery kinetics, and biocompatibility. Specifically: the rigid double helix structure of xanthan gum complements the layered lithium magnesium silicate nanosheets on the recovery timescale. The nanosheets provide initial shaping to prevent sagging, while xanthan gum provides subsequent fusion to ensure film continuity. Hydroxyethyl cellulose and hydroxypropyl methylcellulose are both non-ionic and do not electrostatically associate with the negatively charged xanthan gum and nanosheets, avoiding potential microphase separation. Furthermore, the thermal gelation properties of hydroxypropyl methylcellulose can moderately enhance the network at body surface temperature, further improving anti-sagging properties. Sodium hyaluronate, with its excellent water retention capacity and viscoelastic lubricating properties, enables the coupling film to possess long-lasting wettability, good tactile feel, and molecular-level interfacial adhesion capabilities, and its biocompatibility has been clinically validated over a long period. These four components work synergistically, without any compatibility defects between components or functional overlap or antagonism, achieving an optimal balance of performance across all dimensions. This streamlined composition achieves the full range of performance indicators required for aerosol-type ultrasound coupling agents.
[0051] Further, by weight, it includes 0.05-0.40 parts of shear-thinning polysaccharide, 0.05-0.80 parts of cellulose derivative, 0.005-0.20 parts of water-retaining polymer, 0.01-0.30 parts of layered silicate nanosheets, 12-30 parts of moisturizing acoustic modulator, and 100 parts of water.
[0052] By limiting the ratio of functional components to basic components, shear-thinning polysaccharides, cellulose derivatives, water-retaining polymers, and layered silicate nanosheets can form a stable composite reversible thixotropic network in an aqueous system. Specifically, the shear-thinning polysaccharide provides a flexible chain entanglement structure, resulting in lower flow resistance during aerosol spraying; the layered silicate nanosheets provide a physical cross-linking structure, improving structural recovery after spraying; the cellulose derivative improves the interfacial bonding between the organic components and inorganic sheets, enhancing membrane continuity; and the water-retaining polymer improves the system's water retention capacity, reducing moisture loss during membrane use. Through the synergistic control of these ratio ranges, the aerosol-type ultrasonic coupling agent possesses excellent spraying performance, anti-sagging performance, continuous wetting performance, and stable ultrasonic coupling performance, avoiding problems such as insufficient network structure due to excessively low functional component content, or excessive viscosity and spraying difficulties due to excessively high content.
[0053] Furthermore, the functional components also include a wetting agent and a defoamer. The wetting agent is selected from one or more of poloxamer 188, poloxamer 407, polysorbate, alkyl glycoside, and polyoxyethylene hydrogenated castor oil. The defoamer is selected from one or more of simethicone, polydimethylsiloxane emulsion, dimethicone, and siloxane polyether copolymer. By weight, the wetting agent is 0.01-0.3 parts and the defoamer is 0.005-0.15 parts.
[0054] By adding low amounts of wetting agents and defoamers, the interfacial properties of aerosol-type ultrasonic coupling agents during spraying, spreading, and ultrasonic detection are further improved. The wetting agent reduces the interfacial tension between the coupling agent and the skin surface and the ultrasonic probe surface, improving the spreading ability of the sprayed droplets and enabling discrete droplets to quickly fuse and form a continuous coupling film. The defoamer reduces the stability of microbubbles generated during preparation, filling, and spraying, reducing air entrainment within the coupling film and minimizing ultrasonic reflection and energy loss caused by air interfaces.
[0055] Meanwhile, by limiting the amount of wetting agent and defoamer added, the spray stability and acoustic transmission performance of the aerosol ultrasonic coupling agent can be improved while improving interface wetting and reducing bubble content, avoiding problems such as increased foam, excessive fineness of spray droplets, or impact on the stability of the composite thixotropic network caused by excessive surfactant content.
[0056] Furthermore, the basic components also include one or more of a pH adjuster, a buffer, a chelating agent, or a preservative; wherein the pH adjuster is triethanolamine; the buffer is selected from one or more of a citrate buffer, a phosphate buffer, and a borate buffer; the chelating agent includes disodium edetate; the preservative is one or more of phenoxyethanol, ethylhexylglycerin, or potassium sorbate; and the pH of the aerosol-type ultrasonic coupling agent composition is 6.0-7.2.
[0057] By incorporating a system of pH adjusters, buffers, chelating agents, and preservatives, a stable chemical environment is maintained in the aerosol-type ultrasonic coupling agent during storage and use, thereby improving the long-term stability of the composite thixotropic network. Specifically, triethanolamine regulates the system's pH and improves the hydration state of some polymer components; the buffer reduces pH fluctuations caused by environmental changes, preventing damage to the polymer network structure due to acid-base variations; disodium edetate complexes metal ions in the system, reducing metal ion-induced polymer degradation or abnormal aggregation of inorganic nanosheets; and the preservative inhibits microbial growth, improving product storage stability.
[0058] By controlling the pH of the system within the range of 6.0-7.2, the composite polymer network is kept in a good hydration state and has good compatibility. At the same time, skin contact safety and ultrasound coupling performance are taken into account, avoiding problems such as decreased polymer performance, increased skin irritation, and reduced probe material compatibility caused by excessively acidic or alkaline environments.
[0059] This invention also provides a method for preparing an aerosol-type ultrasonic coupling agent, comprising the following steps: S1, Disperse layered silicate nanosheets in a portion of water to obtain a dispersion; S2, mix the shear-thinning polysaccharide, cellulose derivative and water-retaining polymer, and then mix with the acoustic modulator to obtain a polymer wet material; S3, after mixing the wet polymer material with the dispersion, it is then mixed with the remaining water to obtain an aerosol-type ultrasonic coupling agent; S4, the aerosol ultrasonic coupling agent is stored in the aerosol can through the bag in an isolated manner, and the propellant is filled between the aerosol can and the bag.
[0060] By employing a stepwise construction method to prepare aerosol-type ultrasonic coupling agents, the problems of agglomeration, excessively high local concentration, and uneven network structure caused by different hydration rates of functional components when they are directly added to the aqueous phase are avoided.
[0061] First, layered silicate nanosheets are pre-dispersed in a portion of water to allow them to fully peel off and form a stable layered structure, providing a uniformly distributed structural basis for the subsequent formation of an inorganic thixotropic network. Then, shear-thinning polysaccharides, cellulose derivatives, and water-retaining polymers are pre-wetted with an acoustic modulator to allow the polymer chains to fully unfold, improve their hydration efficiency, and reduce the agglomeration phenomenon caused by direct contact between polymer powders and water.
[0062] By combining the polymer wet material with the layered silicate nanosheet dispersion, the organic polymer network and the inorganic sheet network are fully combined to form a uniform and stable thixotropic structure. This allows the resulting coupling agent to reduce viscosity when subjected to aerosol spray shearing and restore structural strength after spraying, thus possessing both good spraying performance and post-spray film-forming performance.
[0063] This application does not simply mix the components, but rather achieves synergistic effects between functional components through a specific preparation sequence. Since layered silicate nanosheets are inorganic sheet-like materials, their dispersion state directly affects the formation of the final thixotropic network. If added directly along with polymer components, it easily leads to sheet aggregation, preventing the uniform construction of the inorganic network. Meanwhile, shear-thinning polysaccharides, cellulose derivatives, and water-retaining polymers are all polymeric materials that require thorough wetting and hydration to exert their chain entanglement, film formation, and water retention effects. Therefore, this application first forms a nanosheet dispersion, then a wet polymer mixture, and finally performs network composite formation, allowing the functional components to progressively construct a composite thixotropic system according to the structural formation sequence.
[0064] Furthermore, in S3, the polymer wet material is mixed with the dispersion and then matured at a temperature of 20℃-45℃ for 1-24 hours.
[0065] By incorporating a ripening step, sufficient interaction time is allowed between the shear-thinning polysaccharide, cellulose derivative, water-retaining polymer, and layered silicate nanosheets, promoting the formation of a stable physical bond between the organic polymer chains and the inorganic sheets. During the ripening process, the shear-thinning polysaccharide gradually completes molecular chain unfolding and entanglement; the cellulose derivative enhances the continuity of the organic network; the water-retaining polymer improves the system's water-binding capacity; and the layered silicate nanosheets further complete the adjustment of their layered structure.
[0066] By controlling the curing temperature and time, the composite network reaches a stable state, avoiding problems such as sagging of the coupling agent after spraying due to insufficient network formation, or increased spraying resistance due to excessive network enhancement. Curing temperature and time are crucial process parameters for achieving stable formation of the composite thixotropic network in this application. Insufficient curing time results in insufficient physical interaction between functional components, leading to insufficient viscosity recovery. Excessive curing time or temperature can cause a continuous increase in system viscosity, affecting aerosol spraying performance. Therefore, this application limits curing conditions to 20℃-45℃ and 1-24h, ensuring a balance between spraying performance and structural recovery performance in the resulting coupling agent.
[0067] Furthermore, after aging, wetting agents, defoamers, pH adjusters, buffers, chelating agents, and preservatives are added when mixing with the remaining water.
[0068] The order in which the auxiliary components are added in this application is not arbitrary. Adding large amounts of electrolytes, buffer salts, or surfactants before the formation of the functional network may affect the dispersion state of the layered silicate nanosheets and the interactions between polymer chains, thereby reducing thixotropic properties. Therefore, this application chooses to add the auxiliary components after curing, allowing the core functional network to form first, and then further adjusting the wetting, antifoaming, stabilizing, and storage properties of the system through the auxiliary components. Those skilled in the art can obtain a stable aerosol-type ultrasonic coupling agent by following the above steps.
[0069] Further, the aerosol-type ultrasonic coupling agent is degassed and homogenized.
[0070] Because the aerosol-type ultrasonic coupling agent of this application achieves spraying and recovery properties through a composite thixotropic network, its system viscosity is higher than that of ordinary liquid systems, making it easy to introduce air bubbles during the preparation process due to stirring, transfer, and other operations. Therefore, this application includes a degassing step to reduce the air bubble content within the system; simultaneously, a homogenization step is used to improve the uniformity of functional component dispersion, ensuring that the resulting product meets the requirements for aerosol spraying.
[0071] Degassing the prepared aerosol ultrasonic coupling agent removes microbubbles introduced during preparation, stirring, and mixing, reducing air defects within the coupling membrane and improving the continuity of ultrasonic propagation. Homogenization further ensures the functional components are evenly distributed throughout the system, avoiding local viscosity differences and improving spraying stability and batch consistency. Filling processing makes the resulting coupling agent suitable for aerosol packaging systems, enabling convenient spraying and reducing the pollution and waste associated with traditional extrusion-type coupling agents.
[0072] Furthermore, in S1, high-speed shearing at 1000-3000 rpm is used to fully disperse the layered silicate nanosheets; In S2, a low-speed shearing of 300-800 rpm is used to fully composite the shear-diluted polysaccharides, cellulose derivatives, water-retaining polymers, and layered silicate nanosheets to form a stable thixotropic network.
[0073] Furthermore, in S1, the shear rate of the layered silicate nanosheet dispersion stage is 1500-2500 rpm, and the shearing time is 10-30 min; in S2, the shear rate of the composite stage is 400-600 rpm, and the shearing time is 30-60 min.
[0074] The overall preparation process of the aerosol-type ultrasonic coupling agent described in this invention is as follows: S1, Pre-dispersion stage of layered silicate nanosheets First, layered silicate nanosheets are added to a portion of deionized water and pre-dispersed under stirring conditions to fully wet, peel off, and form a uniform dispersion.
[0075] The layered silicate nanosheets are preferably synthesized layered lithium magnesium silicate or layered aluminum magnesium silicate. Since the layered silicate nanosheets need to form a reversible physical network through the layered structure, it is necessary to prioritize their uniform dispersion in the aqueous phase to avoid the formation of layered agglomeration after the subsequent addition of polymer components.
[0076] S2, Functional Polymer Premixing Stage Shear-thinning polysaccharides, cellulose derivatives, and water-retaining polymers are premixed and then wetted with an acoustic modifier to form a polymer wet material.
[0077] Among them, acoustic modifiers are not only used to adjust the acoustic impedance and moisture state of the system, but also to reduce the instantaneous agglomeration caused by direct contact of polymer powder with the aqueous phase, and improve the dispersion uniformity of functional components.
[0078] S3, Composite Thixotropic Network Construction Stage The obtained polymer wet material is slowly added to the layered silicate nanosheet dispersion and mixed under low shear conditions. This causes the shear-thinned polysaccharide to form a flexible polymer network, which in turn allows the cellulose derivative to fill and enhance the organic network structure. The water-retaining polymer is distributed in the network gaps, while the layered silicate nanosheets form an inorganic thixotropic structure.
[0079] The above steps form a reversible thixotropic network.
[0080] Curing stage: The composite system is placed at 20℃-45℃ for 1-24 hours to allow the polymer chain segments to fully unfold and promote the formation of stable physical interactions between the organic network and the inorganic sheets.
[0081] Auxiliary component addition stage: After curing, wetting agents, defoamers, pH adjusters, buffers, chelating agents, and preservatives are added. This post-addition method avoids the auxiliary components affecting the initial dispersion of layered silicate nanosheets and the formation of the polymer network.
[0082] Defoaming, homogenization and filling stages The obtained coupling agent was subjected to vacuum degassing to remove microbubbles from the system; subsequently, homogenization was performed to ensure uniform distribution of the functional components; finally, it was filled into aerosol packaging containers to obtain an aerosol-type ultrasonic coupling agent product. Example 1 This embodiment provides an aerosol-type ultrasonic coupling agent.
[0083] The formulation of the aerosol-type ultrasonic coupling agent in this embodiment, by weight, includes: deionized water: 100 parts; glycerin: 15 parts; xanthan gum: 0.15 parts; hydroxyethyl cellulose: 0.30 parts; sodium hyaluronate: 0.05 parts; and synthetic layered lithium magnesium silicate: 0.10 parts. The preparation method of the aerosol-type ultrasonic coupling agent in this embodiment includes the following steps: (1) Add the synthesized layered magnesium lithium silicate to 30 parts of deionized water and disperse at high speed at 2000 rpm for 20 min to fully wet, peel off and uniformly disperse the layered magnesium lithium silicate to obtain a layered silicate nanosheet dispersion. (2) Mix xanthan gum, hydroxyethyl cellulose and sodium hyaluronate and add them to glycerin. Pre-wet the mixture at 600 rpm for 15 min to fully wet the polymer powder and form a polymer wet material. (3) The obtained polymer wet material was slowly added to the layered silicate nanosheet dispersion and stirred at 500 rpm for 45 min to fully combine the organic polymer network with the inorganic sheet network. (4) Add the remaining deionized water and continue stirring until well mixed; (5) The resulting mixture was allowed to stand at 25°C for 12 h to allow the composite thixotropic network to fully form; (6) The matured coupling agent was degassed under vacuum of -0.07 MPa for 20 min, then homogenized at low speed of 500 rpm for 15 min, and finally filled. (7) Store the aerosol ultrasonic coupling agent in the aerosol can through the bag in an isolated manner, and fill the space between the aerosol can and the bag with propellant.
[0084] Example 2 The difference between this embodiment and Embodiment 1 is that this embodiment further incorporates a cellulose compound system and low-foaming auxiliary components to improve the continuity, wettability, and storage stability of the coupling membrane.
[0085] Specifically, the aerosol-type ultrasonic coupling agent formulation of this embodiment, by weight, includes: deionized water: 100 parts; glycerin: 20 parts; xanthan gum: 0.20 parts; hydroxyethyl cellulose: 0.30 parts; hydroxypropyl methylcellulose: 0.10 parts; sodium hyaluronate: 0.08 parts; synthetic layered lithium magnesium silicate: 0.15 parts; poloxamer 188: 0.05 parts; simethicone: 0.02 parts; disodium edetate: 0.03 parts; phenoxyethanol: 0.50 parts.
[0086] This embodiment uses the same preparation method as Example 1, except that: after the composite thixotropic network has matured, poloxamer 188, simethicone, disodium edetate and phenoxyethanol are added, and the pH of the system is adjusted to 6.5; the maturation temperature is adjusted to 30°C, and the maturation time is adjusted to 18 h.
[0087] By increasing the cellulose compound system, the continuity of the organic network is improved, and the air bubbles generated during the spraying process are reduced by using wetting agents and defoamers, thus improving the spreading performance of the coupling film.
[0088] Example 3 The difference between this embodiment and Embodiment 1 is that this embodiment is mainly used to improve the low bubble performance and continuous film formation performance of the system.
[0089] Specifically, the aerosol-type ultrasonic coupling agent formulation of this embodiment, by weight, includes: deionized water: 100 parts; 1,3-propanediol: 18 parts; xanthan gum: 0.12 parts; hydroxypropyl methylcellulose: 0.35 parts; sodium hyaluronate: 0.10 parts; layered magnesium aluminum silicate: 0.20 parts; alkyl glycoside: 0.03 parts; polydimethylsiloxane emulsion: 0.03 parts; phosphate buffer: 0.05 parts.
[0090] This embodiment uses the same preparation method as Example 1, except that: After the composite thixotropic network is formed and matured, alkyl glycosides, polydimethylsiloxane emulsion, and phosphate buffer are added.
[0091] By incorporating a low-foaming wetting system, the ejected droplets have better spreading ability, while reducing microbubble formation and improving acoustic stability during ultrasonic coupling.
[0092] Example 4 The difference between this embodiment and Embodiment 1 is that this embodiment is used to improve the structural recovery ability and anti-sagging performance after spraying.
[0093] Specifically, the aerosol-type ultrasonic coupling agent formulation of this embodiment includes, by weight, the following: deionized water: 100 parts; polyethylene glycol 400: 12 parts; xanthan gum: 0.25 parts; hydroxyethyl cellulose: 0.40 parts; sodium hyaluronate: 0.10 parts; and layered lithium magnesium silicate: 0.20 parts.
[0094] This embodiment uses the same preparation method as Example 1, except that the curing temperature is adjusted to 40℃ and the curing time is adjusted to 24 h.
[0095] By increasing the degree of thixotropic network formation, the coupling agent can quickly recover its viscosity after jet shearing, thereby improving its retention capacity after spraying and reducing liquid sagging.
[0096] Example 5 The difference between this embodiment and Embodiment 1 is that this embodiment uses different types of functional components to verify the substitutability of the functional components of the present invention. Specifically, the aerosol-type ultrasonic coupling agent formulation of this embodiment, by weight, includes: deionized water: 100 parts; propylene glycol: 15 parts; gellan gum: 0.15 parts; hydroxypropyl cellulose: 0.20 parts; carboxymethyl chitosan: 0.05 parts; layered magnesium aluminum silicate: 0.10 parts.
[0097] This embodiment uses the same preparation method as Example 1.
[0098] Thixotropic networks can also be formed by using different types of shear-degrading polysaccharides, cellulose derivatives, water-retaining polymers, and layered silicate nanosheets.
[0099] Example 6 The difference between this embodiment and Embodiment 1 is that this embodiment is used to verify the lower limit of the content range of the functional components in the claims.
[0100] Specifically, the aerosol-type ultrasonic coupling agent formulation of this embodiment includes, by weight, the following: deionized water: 100 parts; glycerin: 12 parts; xanthan gum: 0.05 parts; hydroxyethyl cellulose: 0.05 parts; sodium hyaluronate: 0.005 parts; and layered lithium magnesium silicate: 0.01 parts.
[0101] This embodiment uses the same preparation method as in Example 1, wherein: the layered magnesium lithium silicate dispersion conditions are 1500 rpm for 10 min; the composite stirring conditions are 400 rpm for 30 min; the curing temperature is 20℃ and the curing time is 1 h.
[0102] This embodiment demonstrates that even with a low content of functional components, it is still possible to form an aerosol-type ultrasonic coupling agent with a certain thixotropic recovery capability.
[0103] Example 7 The difference between this embodiment and Embodiment 1 is that this embodiment is used to verify the upper limit of the content range of the functional components in the claims.
[0104] Specifically, the aerosol-type ultrasonic coupling agent formulation of this embodiment includes, by weight, the following: deionized water: 100 parts; glycerin: 30 parts; xanthan gum: 0.40 parts; hydroxyethyl cellulose: 0.80 parts; sodium hyaluronate: 0.20 parts; and layered lithium magnesium silicate: 0.30 parts.
[0105] This embodiment uses the same preparation method as Example 1, wherein the curing temperature is 45℃ and the curing time is 24h.
[0106] The system obtained in this embodiment has high structural recovery ability and high static viscosity, making it suitable for ultrasonic coupling scenarios that require high dwell performance.
[0107] Example 8 The difference between this embodiment and Embodiment 1 is that this embodiment uses different layered silicate nanosheet materials to verify the substitutability of inorganic thixotropic components.
[0108] Specifically, the aerosol-type ultrasonic coupling agent formulation of this embodiment includes, by weight, the following: deionized water: 100 parts; glycerin: 15 parts; xanthan gum: 0.15 parts; hydroxyethyl cellulose: 0.30 parts; sodium hyaluronate: 0.05 parts; and layered magnesium aluminum silicate: 0.10 parts.
[0109] This embodiment uses the same preparation method as Example 1.
[0110] By replacing layered magnesium lithium silicate with layered magnesium aluminum silicate, the system can still form a stable inorganic layered thixotropic structure, thus verifying that the present invention is not limited to a single inorganic nanosheet material.
[0111] Unless otherwise specified, all samples in the embodiments of this application were prepared under the same conditions and subjected to performance testing after equilibration at 25°C for 24 hours. Each test was repeated three times, and the average value of the test results was taken. The experimental error was controlled within ±5%.
[0112] Test Example 1 Shear-thinning performance test The rheological properties of the aerosol-type ultrasonic coupling agents obtained in Examples 1-8 were tested using a rotational rheometer. The testing instrument was an Anton Paar MCR302 rotational rheometer, using a 40 mm diameter parallel plate test fixture, and the test temperature was controlled at 25°C.
[0113] During the test, at 0.1 s... -1 and 1000 s -1 The apparent viscosity of the samples was determined under shear rate conditions. Each group of samples was tested independently three times, and the average value was taken as the final test result. The test error was controlled within ±5%.
[0114] The shear-thinning characteristics of the aerosol-type ultrasonic coupling agent were evaluated by comparing the viscosity changes of the samples at different shear rates. Specific results are shown in Table 1.
[0115] Table 1. Shear thinning properties test results of samples from Examples 1-8 The aerosol-type ultrasonic coupling agents obtained in Examples 1-8 all exhibited obvious shear-thinning characteristics.
[0116] Among them, Example 6, with the lowest content of functional components, had the lowest initial viscosity, but still maintained a significant shear response; Example 7, with the highest content of xanthan gum, cellulose derivatives, and layered silicate nanosheets, had the highest static viscosity, indicating that increasing the proportion of functional components can enhance the network structure; Examples 1-4 all achieved high adhesion under low shear conditions and reduced flow resistance under high shear conditions. This demonstrates that the thixotropic network constructed in this application can simultaneously satisfy jet flowability and residence stability.
[0117] Test Example 2 Structural recovery performance test The structural recovery performance of the samples was tested using a rotating rheometer in step shear mode.
[0118] The testing steps are as follows: (1) First at 0.1 s -1 Initial viscosity of the sample was tested at the shear rate. (2) Then apply for 1000 s -1 High shear stress for 60 s disrupts the thixotropic network within the system. (3) After shearing stops, the time is restored to 0.1 s. -1 Shear conditions were applied, and the viscosity recovery value was recorded after 60 s.
[0119] Each group of samples was tested three times, and the average value was taken as the test result.
[0120] The structural recovery rate was calculated using the following formula: Recovery rate = (Recovered viscosity / Initial viscosity) × 100%. The test results are shown in Table 2 below.
[0121] Table 2. Test results of structural recovery performance of samples from Examples 1-8 The recovery rates of Examples 1-5 and Example 8 all exceeded 75%.
[0122] Among them, Example 4 showed the highest recovery rate, indicating that a higher content of xanthan gum and layered lithium magnesium silicate can form a stronger reversible physical network. Example 6 showed a decreased recovery rate, indicating that when the functional component was reduced to its minimum range, the network formation ability decreased, but a certain degree of thixotropic recovery performance was still maintained. These results demonstrate that this application does not simply increase viscosity, but rather achieves structural reconstruction after shear failure through polymer chain entanglement networks and layered silicate sheet networks.
[0123] Test Example 3 Spray performance test The spray performance of the aerosol ultrasonic coupling agents obtained in Examples 1-8 was tested using an aerosol valve spraying device.
[0124] The test conditions are as follows: The aerosol valve has a spray pressure of 0.65 MPa and a spray distance of 20 cm.
[0125] The particle size distribution of the ejected droplets was tested using a laser particle size analyzer (Malvern Mastersizer 3000), and the volume average particle size Dv50 of the droplets was recorded.
[0126] Each group of samples was tested 3 times, and the average value was taken.
[0127] Simultaneously observe the continuity of spraying and the state of film formation after spraying.
[0128] Table 3. Spray performance test results of samples from Examples 1-8 In all embodiments, the ejected droplets were larger than 50 μm.
[0129] This demonstrates that the system in this application, due to its high structural recovery capability, can avoid the formation of a large number of fine aerosol droplets. Specifically: Example 2 exhibits the best droplet spreading performance due to the addition of poloxamer 188 to improve interfacial wetting; Example 4 demonstrates the best post-spray retention performance due to the highest thixotropic network strength; Example 7, with its highest viscosity, shows an increase in droplet size, indicating that excessively high structural strength reduces spray refinement. These results verify that this application achieves the technical effect of large droplet ejection and post-spray recovery by controlling the composite network strength.
[0130] Test Example 4 The distribution of air bubbles inside the coupling membrane after ejection was observed using an optical microscope.
[0131] Five fields of view were randomly selected for each sample for image acquisition. The proportion of bubble area to the total area of the observation area was calculated using image analysis software. Each group of samples was tested three times and the average value was taken.
[0132] Table 4. Bubble area ratios in Examples 1-8 Example 3 shows the lowest bubble area.
[0133] Example 3, with the addition of alkyl glycosides and polydimethylsiloxane emulsion, reduced bubble stability during spraying. Example 6, lacking auxiliary components, exhibited the highest bubble ratio. This indicates that wetting agents and defoamers can further improve the low-bubble performance of aerosol coupling agents.
[0134] The experimental results above show that the aerosol-type ultrasonic coupling agent provided in this application constructs a reversible thixotropic network using shear-diluted polysaccharides, cellulose derivatives, water-retaining polymers, and layered silicate nanosheets, resulting in a coupling agent that simultaneously exhibits low jet viscosity and high static viscosity. Under aerosol jet shearing action, the system viscosity rapidly decreases, ensuring smooth jetting; after jetting, the composite thixotropic network can recover its structure, improving film retention. Furthermore, the addition of wetting agents and defoamers further reduces bubble generation during jetting, improving the continuity of the coupling film.
[0135] Examples 1-8 demonstrate that the technical solution of this application is not limited to a single material combination. Under different combinations of shear-thinning polysaccharides, cellulose derivatives, water-retaining polymers, and layered silicate nanosheets, aerosol-type ultrasonic coupling agents with shear-thinning, structure recovery, continuous film formation, and low bubble properties can be obtained.
[0136] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. An aerosol-type ultrasonic coupling agent, comprising a basic component and a functional component, characterized in that, The functional components include shear-thinning polysaccharides, cellulose derivatives, water-retaining polymers, and layered silicate nanosheets; the base components include water and acoustic modifiers; the acoustic modifiers are selected from one or more of glycerol, propylene glycol, 1,3-propanediol, and polyethylene glycol.
2. The aerosol-type ultrasonic coupling agent according to claim 1, characterized in that, The shear-thinning polysaccharide is selected from one or more of xanthan gum, gellan gum, konjac glucomannan, guar gum, modified guar gum, alginate, and carrageenan; The cellulose derivative is selected from one or more of hydroxyethyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose, methyl cellulose, and hydroxypropyl cellulose; The water-retaining polymer is selected from one or more of sodium hyaluronate, potassium hyaluronate, carboxymethyl chitosan, polyglutamate, trehalose polymer, and polyethylene glycol derivatives; The layered silicate nanosheets are selected from one or more of synthetic layered lithium magnesium silicate and layered aluminum magnesium silicate.
3. The aerosol-type ultrasonic coupling agent according to claim 2, characterized in that, The shear-thinning polysaccharide is xanthan gum; the cellulose derivative includes hydroxyethyl cellulose and / or hydroxypropyl methyl cellulose; the water-retaining polymer is sodium hyaluronate; and the layered silicate nanosheets are layered lithium magnesium silicate.
4. The aerosol-type ultrasonic coupling agent according to claim 1, characterized in that, By weight, it includes 0.05-0.40 parts of shear-thinning polysaccharide, 0.05-0.80 parts of cellulose derivative, 0.005-0.20 parts of water-retaining polymer, 0.01-0.30 parts of layered silicate nanosheets, 12-30 parts of moisturizing acoustic modulator, and 100 parts of water.
5. The aerosol-type ultrasonic coupling agent according to claim 1, characterized in that, The functional components further include a wetting agent and a defoamer. The wetting agent is selected from one or more of poloxamer 188, poloxamer 407, polysorbate, alkyl glycoside, and polyoxyethylene hydrogenated castor oil. The defoamer is selected from one or more of simethicone, polydimethylsiloxane emulsion, dimethicone, and siloxane polyether copolymer. By weight, the wetting agent is 0.01-0.3 parts and the defoamer is 0.005-0.15 parts.
6. The aerosol-type ultrasonic coupling agent according to claim 1, characterized in that, The basic components also include one or more of a pH adjuster, a buffer, a chelating agent, or a preservative; wherein the pH adjuster is triethanolamine; the buffer is selected from one or more of a citrate buffer, a phosphate buffer, and a borate buffer; the chelating agent includes disodium edetate; the preservative is one or more of phenoxyethanol, ethylhexylglycerin, or potassium sorbate; and the pH of the aerosol-type ultrasonic coupling agent composition is 6.0-7.
2.
7. A method for preparing an aerosol-type ultrasonic coupling agent as described in any one of claims 1-6, characterized in that, Includes the following steps: S1, Disperse layered silicate nanosheets in a portion of water to obtain a dispersion; S2, mix the shear-thinning polysaccharide, cellulose derivative and water-retaining polymer, and then mix with the acoustic modulator to obtain a polymer wet material; S3, after mixing the wet polymer material with the dispersion, it is then mixed with the remaining water to obtain an aerosol-type ultrasonic coupling agent; S4, the aerosol ultrasonic coupling agent is stored in the aerosol can through the bag in an isolated manner, and the propellant is filled between the aerosol can and the bag.
8. The method for preparing an aerosol-type ultrasonic coupling agent according to claim 7, characterized in that, In S3, the wet polymer material is mixed with the dispersion and then matured. The maturity temperature is 20℃-45℃ and the maturity time is 1-24h.
9. The method for preparing an aerosol-type ultrasonic coupling agent according to claim 8, characterized in that, After aging, wetting agents, defoamers, pH adjusters, buffers, chelating agents, and preservatives are added when mixing with the remaining water.
10. The method for preparing an aerosol-type ultrasonic coupling agent according to claim 7, characterized in that, After obtaining the aerosol-type ultrasonic coupling agent, it is degassed and homogenized.
Citation Information
Patent Citations
Ultrasonic couplant, supporting astringent and preparation methods thereof
CN102451475B
Aerosol type medical ultrasonic coupling agent
CN106039329A
A conjunctival type medical ultrasound coupling agent and its preparation and application methods
CN107854696B
Ultrasonic couplant spray
US11311635B2
